2015
DOI: 10.1245/s10434-015-4706-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Biomarkers in Colorectal Cancer: Implications for the Clinical Surgeon

Abstract: Colorectal cancer is a heterogeneous disease with a wide range of long-term outcomes and responses to treatment. Recent advances in the genetic and molecular characterization of tumors has yielded a set of prognostic and predictive biomarkers that aid the identification of patients at higher risk for disease recurrence and progression, and in some cases indicate the likelihood of response to a specific treatment. Increasingly, these biomarkers have become integral to the treatment algorithm for managing patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 234 publications
0
25
0
Order By: Relevance
“…In the past few decades, many clinicopathological biomarkers have been identified to efficiently predict recurrence and survival in CRC through the continuous efforts of researchers [44]. However, expensive and technical limitations have prevented their clinical spread.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, many clinicopathological biomarkers have been identified to efficiently predict recurrence and survival in CRC through the continuous efforts of researchers [44]. However, expensive and technical limitations have prevented their clinical spread.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several possible additional factors associated with recurrence. Patient factors, like intake of coffee and alcohol, smoking, weight-loss and Glascow Prognostic score [2] [3] [4] [5] [6], treatment factors like surgical experience and technique [7] [8], tumor factors like location, differentiation, vein-, nerve-and lymphatic ingrowth [9] [10] and molecular factors [11] [12] [13] [14] have been shown to influence cancer recurrence, and adjuvant oncological therapy is often recommended. In the present study, we have taken interest in what consequences repeated or aggravated inflammatory stress will inflict on the patient and influence the risk of recurrence after potential curative resection of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence rate is higher than 11 and 40-50% in postoperative patients with stage II and III CRC, respectively (3). The high recurrence rate of CRC is a major contributor to poor prognosis, and poor prognosis in patients with CRC is associated with tumor invasion and metastasis (4,5). The development of metastasis is complex, and includes proliferation, angiogenesis, invasion, detachment, migration, adhesion and extravasation into target organs (4).…”
Section: Introductionmentioning
confidence: 99%
“…The development of metastasis is complex, and includes proliferation, angiogenesis, invasion, detachment, migration, adhesion and extravasation into target organs (4). Research investigating the mechanism into the origin and development of CRC has identified a high number of biomarkers, as well as identifying signaling pathways that are vital for tumorigenesis and progression of CRC (5). However, only a few of the identified biomarkers have clinicopathological significance in CRC.…”
Section: Introductionmentioning
confidence: 99%